FACTORS AFFECTING STUDENTS’ IN SELECTING THE ACCOUNTING STUDY PROGRAM IN ITB AAS INDONESIA - Tira Nur Fitria; Budiyono Budiyono (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The increasing interest in the Accounting study program at various Indonesian universities proves that accounting science is important. It is interesting to discuss to find out the factors behind it. The purpose of this study was to find the factors that influence the students’ decision in selecting an Accounting study program at ITB AAS Indonesia. This research is descriptive qualitative. The result of the analysis shows that several intrinsic and extrinsic factors affect the students in selecting the Accounting study program. In intrinsic factors shows that the students having an interest in deepening or improving their Accounting knowledge, choosing the study program based on their wishes, feeling that the Accounting study program has great opportunities in their works, choosing Accounting study program to get a good or better job after graduating from college later, having a desire to become a financial staff, a professional accountant or other job related to Accounting at work later, also feeling that Accounting study program attract their attention. While, the extrinsic factors show that: the students do not choose a study program because of a recommendation from their school, their wishes from parents or family, or following their friends who also take the same study program. But, the students choose An Accounting study program because the reputation of the study program at the campus is